(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
This article intends to trace the history of behavioral couple therapy in the literature. The major divisions between the different approaches are commented, as well as the technical contributions of each of them. Applied Behavior Analysis introduced a functional model to analyze sequences of exchanges between partners and an operant technology to modify them. Cognitive-Behavior Therapy brought a cognitive model that made it possible to work in a focused way with expectancies, attributions and beliefs in couple interaction. Clinical Behavior Analysis contributed with acceptance technology and its focus on context and the promotion of the intense experience of interaction. Besides the innovations of each generation, a certain continuity of ideas is observed. And techniques like communication training and problem solving training that unite behavioral couple therapy throughout its diversity of schools, make explicit the basic presumption that making a relationship work needs to be learned.